Novel Functional Whey-Based Drinks with Great Potential in the Dairy Industry - Pereira, Carlos (2015)
This work focuses on the production of liquid whey protein concentrates by ultrafi ltration followed by thermal denaturation and homogenization of the ultrafi ltrated concentrate, as well as on the production of ultrafi ltrated permeates concentrated by reverse osmosis. Kefir grains (fresh and thawed) and/or commercial probiotic bacteria were inoculated in both liquid whey protein concentrates and concentrated ultrafi ltrated permeates and grown at 25 °C for 24 h for the manufacture of fermented drinks. The physicochemical characterization (pH, titratable acidity, viscosity, and content of total solids, ash, fat and proteins) of the obtained drinks was then assessed and compared. Enumeration of viable microorganisms was carried out immediately aft er inoculation (at 0 h), during the fermentation period (at 12 and 24 h) and during refrigerated storage (at 48, 168 and 336 h). The fermented drinks showed acceptable physicochemical and sensorial properties, and contained above 7 log CFU/mL of lactococci and lactobacilli and 6 log CFU/mL of yeasts aft er 14 days of refrigerated storage, which is in agreement with the standards required by international organizations like European Food Safety Authority (EFSA) and Food and Drug Administration (FDA) for products containing probiotics. In summary, the strategy developed in this work contributes to the expansion of the applications of products derived from whey fractionation for the design of novel functional foods.